2021
DOI: 10.21203/rs.3.rs-324238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public awareness and acceptance of COVID-19 vaccine: An online cross-sectional survey, conducted in the first phase of vaccination drive in India

Abstract: The context-specific, complex issue of ‘vaccine hesitancy’ is explicated in terms of delay or refusal of vaccination despite the availability of vaccine services. Although eleven million beneficiaries were administered the COVID-19 vaccine in India from 16th January 2021 till 20th February 2021, however, proportionately a low turnout has been registered in various parts of the country, possibly attributable to hesitance/apprehension towards the current vaccination. In this backdrop, we report the response (col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…In total 1035 respondents, only 1016 respondents' provided consent to participate in the study but 19 respondents did not give consent so finally, we included the 1016 respondents for our study to make the results. In total 1016 respondents, 52% are male and 47.6% are female; this shows that almost equal representation of either gender was registered which is supported by the study conducted by Arumuganair [4].…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…In total 1035 respondents, only 1016 respondents' provided consent to participate in the study but 19 respondents did not give consent so finally, we included the 1016 respondents for our study to make the results. In total 1016 respondents, 52% are male and 47.6% are female; this shows that almost equal representation of either gender was registered which is supported by the study conducted by Arumuganair [4].…”
Section: Resultssupporting
confidence: 61%
“…The participation was primarily documented from 26 states with maximum representation from 40.9% from Karnataka, 10.9% from Andhra Pradesh, 8.3% from West Bengal, 6.6% from Telangana, 4.2% from Tamil Nadu, and rest from remaining states. Majority of the participants are from urban area these results were supported by the study conducted by Arumuganair [4] and comorbidity conditions show that 88.1% of respondents do not have any health problem.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…[ 4 5 18 ] Other two similar studies conducted in India reported about 70% were willing to get vaccinated, where the inclination is less than that reported in the present study. [ 3 19 ] A cross-sectional study conducted in Kerala among 213 participants reported 80.2% were ready to take vaccine. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%